ANALISIS KUANTITATIF TES BUATAN GURU GEOGRAFI BERDASARKAN MODEL LOGISTIK DUA PARAMETER (L2P) TEORI RESPONSI BUTIR DI KABUPATEN PADANG PARIAMAN - Zamhar Bakri (JURNAL PENDIDIKAN ROKANIA, 2019)
The type of research used was descriptive quantitative with the population in the form of items tested to participants who took the exam from January to June 2013/2014, while the sample as respondents was class X SMA Pariaman Regency, amounting to 1012 people, Data collection techniques namely the study of documents, in the form of LJK data for participants of the January-June 2013/2014 exam along with the answer key. Before the item is carried out, it is necessary to test the TRB requirements, namely in the form of dimensions with factor analysis. Parameter invariance problem with correlation analysis and local independence with covariance analysis. After fulfilling the three requirements, then it can be determined the level is difficult by using the Ascal 3.2 program and the function of item information. test results on the requirements of the TRB obtained that (1) the results of the validity test there are 33 valid questions and 17 items that drop, (2) the reliability of the test with the results are not reliable with a value of 0.55 (3) the local independence is the smallest covariance index and close to zero in the diagonal cell of the matrix. Analysis of the level of difficulty and power difference found that there were 33 items (66%) acceptable, 17 items (34%) were rejected. The value of the information function is good, because it is difficult for most of the levels to be at (-2 ≤ bi ≥ 2). Based on the findings of this author, it is recommended that the choice of answers, pictures and sentences used be corrected, and in accordance with SKL